2013
DOI: 10.2174/1871520611313040005
|View full text |Cite
|
Sign up to set email alerts
|

Cell Survival Signaling in Neuroblastoma

Abstract: Neuroblastoma is the most common extracranial solid tumor of childhood and is responsible for over 15% of pediatric cancer deaths. Neuroblastoma tumorigenesis and malignant transformation is driven by overexpression and dominance of cell survival pathways and a lack of normal cellular senescence or apoptosis. Therefore, manipulation of cell survival pathways may decrease the malignant potential of these tumors and provide avenues for the development of novel therapeutics. This review focuses on several facets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 134 publications
0
30
0
Order By: Relevance
“…Another protein firmly involved in angiogenesis of neuroblastoma is vascular endothelial growth factor (VEGF) (5,6). As expected, one of the control levels is transcription-related to the interaction between IL-8 and VEGF promoters and different transcription factors, such as NF-κB, AP-1 and C-EBP/NF-IL-6 (7)(8)(9)(10)(11)(12). In addition, the expression of IL-8 and VEGF genes may be under the control of epigenetic mechanisms, such as those regulated by microRNAs in cancer, differentiation and inflammatory processes (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 68%
“…Another protein firmly involved in angiogenesis of neuroblastoma is vascular endothelial growth factor (VEGF) (5,6). As expected, one of the control levels is transcription-related to the interaction between IL-8 and VEGF promoters and different transcription factors, such as NF-κB, AP-1 and C-EBP/NF-IL-6 (7)(8)(9)(10)(11)(12). In addition, the expression of IL-8 and VEGF genes may be under the control of epigenetic mechanisms, such as those regulated by microRNAs in cancer, differentiation and inflammatory processes (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 68%
“…Our study was focused on the genes identified as prognosis markers and potential therapeutic targets of neuroblastoma [4, 5, 21, 23, 24]. Concerning poor prognosis factors, when gene expression was modulated by both citalopram and escitalopram, the action was always a decrease except for MDM2 and VEGFA .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis of tumor samples performed in the last two decades correlated these prognostic disparities to an extensive series of genetic features actually considered as the prognosis markers of the disease notably MYCN [4, 5]. Those associated with a poor clinical outcome have become the potential targets for the development of new therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…1 Unfortunately, 5-year overall survival rates are still only around 60% for RA-treated patients. [7][8][9] Frequently, overactivation of survival pathways prevents cell-cycle arrest or apoptosis in neuroblastoma cells (reviewed by Megison et al 10 ). [7][8][9] Frequently, overactivation of survival pathways prevents cell-cycle arrest or apoptosis in neuroblastoma cells (reviewed by Megison et al 10 ).…”
Section: Introductionmentioning
confidence: 99%